Nilai Guna (Kepuasan) Green Technology E-Toll sebagai Salah Satu Alternatif Layanan pada Konsumen Pengguna Tol dalam Kota Jakarta - Sriwardiningsih, Enggal (Bina Nusantara University, 2014)
Consumer satisfaction should be provided by organization. The Government service in the form of etoll green technology is an alternative service in toll road for public. This service is still new in the implementation. Therefore, it is necessary to do a study in the level of elasticity of the e-toll service. Consumer satisfaction from toll users becomes a measure of the success rate from this service. Consumer satisfaction from toll users who use e-toll will be achieved if they are satisfied with the e-toll product and GTO service. This study aims to test a model that explains consumer satisfaction from e-toll users. The theory underlying this study was service quality and satisfaction. The study was conducted on the toll roads in Jakarta. Unit analysis was e-toll users. Samples were taken based on convenient sampling. Structural Equation Modelling used SPSS 16.0 software and elasticity formula was used to test the hypothesis; while the implication for transport domain.